Síntesis de complejos de Ni con ligandos carbeno N- Heterocíclico. Aplicación en reacciones de acoplamiento C-C de Suzuki - Carrera Cevallos, Jeanette Verónica (2022)
Metalodendrymers are very important compounds in the area of catalysis. In the present study, dendritic nickel organometalic compounds with N-heterocyclic carbene ligands are synthesized, using Frechét-type poly (aryl ether) dendrons. The prepared compounds were used to apply them in catalytic processes such as the Suzuki reaction for C-C couplings. The present study proposes the structural analysis of the compounds by spectroscopic and crystalographic techniques, as well as the performance of this type of catalyst in the Suzuki coupling reaction followed by chromatographic techniques, it was concluded that dendritic nickel organometallic compounds with ligands N-heterocyclic carbene are obtained with yields greater than 80%, they present cis-trans isomerism, according to the relative position of the ligands in the square-plane environment of nickel, as well as the syn-anti isomerism due to the slow rotation around to the Ni-C axis and the position of the mesityls located on both carben ligands or on opposite sides of the complex plane. The activity of the catalyst in the Suzuki coupling reaction decreases in the second cycle, despite this it reaches a conversion of 72% in 120 minutes.